Evaluation of serum irisin levels in patients with endometrial hyperplasia: A controlled cross-sectional study - Şahin, Erdem; Eraslan Şahin, Mefküre; Madendağ, Yusuf; Çöl Madendağ, İlknur; Tayyar, Ahter Tanay; Gözüküçük, Murat; Karakükçü, Ciğdem; Açmaz, Gökhan (Journal of Surgery and Medicine, 2019)
Aim: Irisin, which is proteolytically splited form of fibronectin type III domain containing 5 (FNDC5), is a protein with 112 amino acid. Irisin is an exercise-induced hormone excreted primarily by cardiac muscle and skeletal cells which can be described as an exercise hormone and a new potential target for the treatment of metabolic diseases and obesity. Our goal was to evaluate the serum irisin levels in patients with endometrial hyperplasia (EH). Methods: An observational study is planned. The study population consisted of two groups: 1) the EH group (study group), consisting of participants who had been histopathologically diagnosed with simple EH without atypia and 2) the control group, consisting of healthy participants admitted to the clinic for an annual examination without any complaints or symptoms. Primary outcome of the study was evaluation irisin status. Serum irisin levels were determined by an enzyme-linked immunosorbent assay (ELISA) method. Results: After sample size analysis, 52 participants enrolled into the study as study group (EH group) (n=26) and control group (n=26). The mean age was 39.5±3.8 years in the EH group and 40.7±2.4 years in the control group (p=0.258). Mean BMI was 28.8±2.1 kg/m2 in the EH group and 28.5±1.2 kg/m2 in the control group (p=0.666). Gravidity, parity, systolic blood pleasure, diastolic blood pleasure, fasting glucose levels, smoking status, alcohol use were similar for both groups (p=0.499, p=0.278, p=0.248, p=0.424, p=0.646, p=0.486 and p=0.153, respectively). In control group regular exercise rates was significantly higher than EH group (26.9%, 3.84%, respectively p<0.001). The mean serum irisin level was 1.9±0.7 μg/ml in the EH group and 3.5±2.0 μg/ml in the control group. Serum irisin levels were found to be significantly lower in the EH group compared to the control group (p<0.001). Conclusion: The data from the current study indicate that serum irisin levels were significantly decreased in patients with endometrial hyperplasia. Serum irisin levels may open up new horizons for therapeutic targets for the treatment of patients with EH.